Hedonic and Utilitarian Consumption in COVID-19 Process - Murat Seyfi (Erciyes University, 2021)
Due to globalization, competitive marketing strategies, and developments in communication technologies, analyzing consumer behaviors becomes much more complicated these days. Fundamentally, the most noteworthy factors that affect consumer behaviors are getting benefits, entertainment, feeling satisfied, and taking pleasure. Analyzing consumer behaviors and developing new strategies becomes crucial for companies during the COVID-19 period that turns daily life upside down. This study aims to investigate if there is a difference between hedonic and utilitarian consumption behaviors of participants who have a high- and low-level fear of COVID-19. The aims of former researches that were carried out up to the present were to find reasons and effects of hedonic consumption. Since this study aims to investigate hedonic and utilitarian consumption from the perspective of COVID-19 fear, which is an ultimate crisis, this study differs from other studies. An online questionnaire is selected as the research method of this study and the sample involves 548 (N=548) individuals. The research showed that there is a statistically significant difference among participants who have a high and low level of COVID-19 fear in terms of hedonic and hedonic and utilitarian consumption behaviors. Research results and limitations are discussed within the context of the literature.